Visceral adiposity, insulin resistance and cancer risk - REYNOLDS, JOHN; DONOHOE, CLAIRE (My University, 2011)
Background: There is a well established link between obesity and cancer. Emerging research is characterising this relationship further and delineating the specific role of excess visceral adiposity, as opposed to simple obesity, in promoting tumorigenesis. This review summarises the evidence from an epidemiological and pathophysiological perspective. Methods: Relevant medical literature was identified from searches of PubMed and references cited in appropriate articles identified. Selection of articles was based on peer review, journal and relevance. Results: Numerous epidemiological studies consistently identify increased risk of developing carcinoma in the obese. Adipose tissue, particularly viscerally located fat, is metabolically active and exerts systemic endocrine effects. Putative pathophysiological mechanisms linking obesity and carcinogenesis include the paracrine effects of adipose tissue and systemic alterations associated with obesity. Systemic changes in the obese state include chronic inflammation and alterations in adipokines and sex steroids. Insulin and the insulin-like growth factor axis influence tumorigenesis and also have a complex relationship with adiposity. There is evidence to suggest that insulin and the IGF axis play an important role in mediating obesity associated malignancy. Conclusions: There is much evidence to support a role for obesity in cancer progression, however further research is warranted to determine the specific effect of excess visceral adipose tissue on tumorigenesis. Investigation of the potential mechanisms underpinning the association, including the role of insulin and the IGF axis, will improve understanding of the obesity and cancer link and may uncover targets for intervention.
PUBLISHED
Keywords: Oncoloogy; obesity; Cancer